Pyrolysis of Spirulina platensis, Tetradesmus obliquus and Chlorella vulgaris by TG-FTIR and Py-GC/MS: Kinetic analysis and pyrolysis behaviour. (1st April 2022) - Kong, Wenwen; Shen, Boxiong; Ma, Jiao; Kong, Jia; Feng, Shuo; Wang, Zhuozhi; Xiong, Lifu
Abstract: The pyrolysis characteristics of Spirulina platensis ( S. platensis ), Tetradesmus obliquus ( T. obliquus ) and Chlorella vulgaris ( C. vulgaris ) were investigated by thermogravimetric-infrared spectrometry (TG-FTIR), pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), and kinetic models. The elemental and biochemical composition of different microalgae obviously influenced their pyrolysis behaviour. The results indicated that the pyrolysis process of the three microalgae could be divided into drying, fast pyrolysis and carbonization stages. The major pyrolysis reaction of microalgae occurred between 500 K and 600 K. TG-FTIR results showed that the pyrolysis of S. platensis produced more CO2 and compounds containing CO bonds than the products of pyrolysis of T. obliquus and C. vulgaris, which related to the high content of C in S. platensis . The apparent activation energies, according to kinetic analysis, followed the trend C. vulgaris (173.24–404.13 kJ mol −1 )> S. platensis (173.96–329.89 kJ mol −1 )> T. obliquus (151.39–289.95 kJ mol −1 ). Py-GC/MS analysis indicated that amines, amides, and other nitrogen-containing compounds produced by the pyrolysis of S. platensis have the highest mass fraction, which is attributed to its high N and protein contents. In contrast, relating to lipid contents, hydrocarbons produced from T. obliquus and C. vulgaris are slightly higher than those produced from S. platensis . Graphical abstract: Image 1 Highlights: Wastewater cultured algae were pyrolyzed to evaluate its bioenergy potential. Pyrolytic products were analysed using TG-FTIR and Py-GC/MS. Pyrolysis of S. platensis produced more H2 O, CO2, and CO compounds. Kinetic and pyrolysis reaction mechanism was interpreted.